(untitled) (International Seven Journal of Multidisciplinary, 2024)
The Family Health Strategy (ESF) translates into the introduction of a preventive care model, oriented towards the family in its physical and social environment as the nucleus of action, with the aim of promoting health. The actions carried out within the context of this health service, which is the population’s gateway to Primary Health Care (PHC), are the responsibility of a minimum ESF team, made up of a doctor, nurse, nursing technician and Community Health Agents (ACS), the latter of whom occupy a more prominent position, given their responsibility for establishing the link between users and this public health service. Given the relevance of this professional category to the work process of the Family Health Strategy, this investigation proposes a reflection on the work of this professional in the current public health policy. The results discussed here come from a narrative review and documentary research carried out between May 2022 and November 2023. By analyzing the research identified, it was possible to confirm the importance of CHAs in carrying out the work proposed in the context of Primary Health Care. The National Primary Health Care Policy (PNAB) of 2017 was a marker that brought harm to the work process of this professional, since it weakened the work of health education by assigning clinical duties to this professional.